Combined HDAC and BET inhibition enhances melanoma vaccine immunogenicity and efficacy - Badamchi-Zadeh, A; Moynihan, K; Larocca, R; Aid, M; Provine, N; Iampietro, M; Kinnear, E; Penaloza-Macmaster, P; Abbink, P; Blass, E; Tregoning, J; Irvine, D; et al. (American Association of Immunologists, 2018)
The combined inhibition of histone deacetylases (HDAC) and the proteins of the bromodomain and extraterminal (BET) family have recently shown therapeutic efficacy against melanoma, pancreatic ductal adenocarcinoma, testicular, and lymphoma cancers in murine studies. However, in such studies, the role of the immune system in therapeutically controlling these cancers has not been explored. We sought to investigate the effect of the HDAC inhibitor romidepsin (RMD) and the BET inhibitor IBET151, both singly and in combination, on vaccine-elicited immune responses. C57BL/6 mice were immunized with differing vaccine systems (adenoviral, protein) in prime-boost regimens under treatment with RMD, IBET151, or RMD+IBET151. The combined administration of RMD+IBET151 during vaccination resulted in a significant increase in the frequency and number of Ag-specific CD8+ T cells. RMD+IBET151 treatment significantly increased the frequency of vaccine-elicited IFN-γ+ splenic CD8+ T cells and conferred superior therapeutic and prophylactic protection against B16-OVA melanoma. RNA sequencing analyses revealed strong transcriptional similarity between RMD+IBET151 and untreated Ag-specific CD8+ T cells except in apoptosis and IL-6 signaling-related genes that were differentially expressed. Serum IL-6 was significantly increased in vivo following RMD+IBET151 treatment, with recombinant IL-6 administration replicating the effect of RMD+IBET151 treatment on vaccine-elicited CD8+ T cell responses. IL-6 sufficiency for protection was not assessed. Combined HDAC and BET inhibition resulted in greater vaccine-elicited CD8+ T cell responses and enhanced therapeutic and prophylactic protection against B16-OVA melanoma. Increased IL-6 production and the differential expression of pro- and anti-apoptotic genes following RMD+IBET151 treatment are likely contributors to the enhanced cancer vaccine responses.